2013
DOI: 10.1159/000354217
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Stenosis and Atrial Fibrillation Influence Plasma Fibulin-1 Levels in Patients Treated with Coronary Bypass Surgery

Abstract: Objectives: Aortic valve stenosis (AS) causes cardiac fibrosis and left ventricular hypertrophy, and over time heart failure can occur. To date, a reliable marker to predict progression of AS or the development of heart failure is still lacking. In this study, we addressed the hypothesis that fibulin-1 levels reflect myocardial fibrosis. Methods: Patients undergoing heart surgery at the Odense University were investigated. By 2012 data on outcome were obtained. Results: In 293 patients, plasma fibulin-1 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…However, no association was shown in the multivariable analyses. This is partly in accordance with data from patients with aorta stenosis, where fibulin-1 levels were related with S’, but not with LVEF [10]. Furthermore, we demonstrated a moderate, inverse association with eGFR which could blunt a potential weaker association with LV contractile reserve.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no association was shown in the multivariable analyses. This is partly in accordance with data from patients with aorta stenosis, where fibulin-1 levels were related with S’, but not with LVEF [10]. Furthermore, we demonstrated a moderate, inverse association with eGFR which could blunt a potential weaker association with LV contractile reserve.…”
Section: Discussionsupporting
confidence: 92%
“…Fibulin-1 is an extracellular matrix glycoprotein and is considered to reflect pathological accumulation of extracellular matrix components surrounding vascular smooth muscle cells [10]. To our knowledge no previous studies of fibulin-1 in HFrEF patients have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…FBLN1 levels are increased in serum and bronchoalveolar lavage fluid of asthma patients (Lau, et al, 2010) and in the plasma and lung tissue of IPF patients (Jaffar, et al, 2014). Based on our results, we observe an association between FBLN1 and fibrotic diseases; this is also corroborated in existing bibliography (Ge, et al, 2015;Hansen, et al, 2013;Jaffar, et al, 2012) regarding specific tissues (e.g., lung, myocardium). We suggest that further proteomics analyses should be performed to measure the quantity of the fibulin-1 translated protein in the related fibrotic tissues and its potential involvement in fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, Hansen et al study FBLN1 with regard to myocardial fibrosis. In (Hansen, et al, 2013), they suggest that, since Aortic Valve Stenosis (AVS) causes cardiac fibrosis and since they observe elevated expression of the FBLN1 gene in AVS samples against controls, the FBLN1 must be expressed as part of the fibrotic process. Even though FBLN1 is undeniably implicated in various fibrotic diseases, its expression levels in different tissues and its actual role regarding different fibrotic diseases should be further tested.…”
Section: Key Fibrosis-related Genesmentioning
confidence: 99%
“…Beyond LV hypertrophy development of fibrosis plays a role in myocardial remodeling in AS. Although we can only speculate on the degree of myocardial fibrosis, we have recently shown that fibulin-1 levels were elevated in patients with known AF undergoing cardiac surgery compared to patients with sinus rhythm [19]. Additionally, we have demonstrated that fibulin-1 levels correlated with echocardiographic indices of myocardial stiffness and increased filling pressures suggesting that fibulin-1 might be a marker of myocardial fibrosis.…”
Section: Discussionmentioning
confidence: 83%